1969
DOI: 10.1021/bi00831a033
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the conformation and interaction in dinucleoside mono- and diphosphates by proton magnetic resonance

Abstract: Gallard-Schlesinger, Long Island, N. Y., was the source of ApA, CpA, CpG, and CpC. The following compounds were obtained from Miles Chemical Co., Elkhart, Ind.: UpG, ApAp!, and UpUp (2',3'). ApAp (2',3') was obtained from the alkaline partial hydrolysate of poly A after fractionation through a DEAE-cellulose column.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(71 citation statements)
references
References 53 publications
9
62
0
Order By: Relevance
“…(a) Kondo, Schweizer & Halles, 1969). The conformational rigidity of the nucleoside portion is obscured when one does not discriminate 5'-nucleotides from Y-nucleotides and nucleosides.…”
Section: The Conformation Of the Nucleoside Portion In Nucleotides Ismentioning
confidence: 99%
“…(a) Kondo, Schweizer & Halles, 1969). The conformational rigidity of the nucleoside portion is obscured when one does not discriminate 5'-nucleotides from Y-nucleotides and nucleosides.…”
Section: The Conformation Of the Nucleoside Portion In Nucleotides Ismentioning
confidence: 99%
“…Since the pioneering efforts of Jardetzky (12) and Lemieux (13), it has been demonstrated that n.m.r. studies can provide detailed conformational information at the nucleoside (14-201, nucleotide (21-30), and dinucleoside monophosphate level (23,(31)(32)(33)(34)(35)(36). 'Presented in part at the 4th Harry Steenbock Symposium on the "Structure and Conformation of Nucleic Acids and Protein -Nucleic Acid Interactions", Madison June 16-19,1974.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum ratio of the drug molecules participating in tile complex in this ~tndy is 1 per 4 bases, both in the case of poly A and poly C. The chemical shift toward lower fields of adenine in poly A is consistent with the intercalation. The ft-2 and H-8 aromatic protons are normally shifted t,~-ward higher fields in the polynucleotides [8,9] due to the ring currents of the neighbors. Intercalation of tile drug molecule between bases will decrease the effect of the neighboring bases, hence will shift the proton resonances toward lower fields.…”
Section: Discussionmentioning
confidence: 99%